2019
DOI: 10.1021/acs.jafc.9b03517
|View full text |Cite
|
Sign up to set email alerts
|

Thymol Mediates Bactericidal Activity against Staphylococcus aureus by Targeting an Aldo–Keto Reductase and Consequent Depletion of NADPH

Abstract: Staphylococcus aureus is a common pathogen that can cause life-threatening infections. Treatment of antibioticresistant S. aureus infection needs effective antibacterial agents. Thymol, a generally recognized safe natural compound, has potential as an alternative to treat S. aureus infections. However, the targets and mechanisms of action of thymol were not fully understood. Bioinformatics analysis showed that IolS, a predicted aldo−keto reductase (AKR) in S. aureus, could be a potential target of thymol. Isot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 55 publications
3
29
0
Order By: Relevance
“…T-CNM causes cell membrane shrinkage and invagination, while THY results in perforation in cell membrane. Zhou et al (2019) reported that THY interacted with the potassium ion channel protein β subunit-KcNAb on the inner side of the cell membrane, resulting in perforation injury of the cell membrane of S. aureus. Whether THY causes the perforated membrane injury of Z. rouxii through the reported mechanism still needs further confirmation in the future work.…”
Section: Sem Observationmentioning
confidence: 99%
“…T-CNM causes cell membrane shrinkage and invagination, while THY results in perforation in cell membrane. Zhou et al (2019) reported that THY interacted with the potassium ion channel protein β subunit-KcNAb on the inner side of the cell membrane, resulting in perforation injury of the cell membrane of S. aureus. Whether THY causes the perforated membrane injury of Z. rouxii through the reported mechanism still needs further confirmation in the future work.…”
Section: Sem Observationmentioning
confidence: 99%
“…The traditional Chinese medicine, 2-isopropyl-5-methylphenol (IPMP), commonly known as thymol, is a monoterpene phenol isolated from plants. It is a component of the essential oils extracted from various plants in the Lamiaceae, Verbenaceae, and Scrophulariaceae families, and it exhibits anti-inflammatory, antioxidant and potent antimicrobial properties [22][23][24]. In our previous studies [25] we showed the potent effects of thymol against MRSA infections.…”
Section: Introductionmentioning
confidence: 99%
“…It is classified as a generally recognized as safe (GRAS) compound by the US Food and Drug Administration. It possesses notable antimicrobial activities against bacteria and fungi [76], and is used in edible films [77] and other areas. In phenolic compounds, the main identified compound was quercetin (Figure 1).…”
Section: The Most Important Compounds Identified and Their Propertiesmentioning
confidence: 99%